TRANSFORMASI PEMBELAJARAN: MENJEMBATANI DIGITAL LEARNING DAN MODEL KONVENSIONAL - Isti Sufiana; Daryati; Agusti Purwani; Fisti Sucia (As-Sulthan Journal of Education, 2025)
The advancement of information and communication technology has significantly transformed the education sector, particularly in how learning processes are conducted. Digital learning has emerged as both an alternative and a challenge for modern education systems, especially when compared to conventional teaching approaches. This study aims to explore the basic concepts of digital learning and its differences from traditional education, while identifying its advantages, challenges, and impacts on teaching and learning. A qualitative method with a literature study approach was used, analyzing scholarly journals, articles, and research reports from credible sources to gain in-depth insights. The findings reveal that digital learning offers flexibility, personalized learning, and broad access to information, yet presents challenges such as technological access gaps, low digital literacy, and the need for pedagogical adaptation by educators. Meanwhile, conventional learning still excels in fostering direct interaction and reinforcing social values. These findings underscore the importance of integrating both digital and traditional approaches to create a more adaptive and inclusive learning model. This study contributes to guiding educational transformation toward a system that aligns with 21st-century demands.